PENGARUH PENGGUNAAN METODE SQ3R (SURVEY, QUESTION, READ, RECITED, REVIEW) TERHADAP KEMAMPUAN MEMBACA INTENSIF SISWA KELAS 4 SDN TAMBAKROMO 1 GENENG - Gita Deva Tri Nuryani; Widya Trio Pangestu; Prima Rias Wana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The aim of the researchers in this study was to improve students' intensive reading skills at SD Negeri Tambakromo 1 Geneng in Indonesian subjects. This study uses a quantitative method (experimental) with a one group pretest-posttest design. This study uses interviews and tests. The result of the interview is that the students' reading ability is good but there are 8 students who have low reading ability. The method used by the teacher is a lecture in every lesson. The learning outcomes of students who reached the KKM were only 15 students in intensive reading learning. From the research results tcount> t table = 8.419> 1756 SQ3R method has a significant effect on intensive reading ability in 4th grade students of SDN Tambakromo 1. Because if t Count > tTable then it means, H0 is rejected and Ha is accepted. Likewise with the results of the significance of Sig.(2-tailed) is 0.015, the result is less than 0.05 then H0 is rejected and Ha is accepted. SQ3R method has a significant effect on intensive reading ability in grade 4 students at SDN Tambakromo 1.